Knowledge, attitudes, and practices regarding nutrition among patients with malignant tumors - Ren, Yuejun; Li, Jie; Wu, Jingjing; Niu, Qiaohong; Ren, Xiaolu; Ren, Qiaoli (Frontiers in Nutrition, 2026)
ObjectivesThis study aimed to investigate the knowledge, attitudes, and practices (KAP) regarding nutrition among patients diagnosed with malignant tumors.MethodsA cross-sectional survey was conducted from 16 October 2023 to 30 April 2024, in author’s hospital. Demographic information and KAP were collected through structured questionnaires.ResultsThe study analyzed 535 patients. Males were 370 (69.16%), and 213 (39.81%) reported nutritional supplement use. The mean (±SD) scores were 10.88 ± 6.02 for knowledge, 15.46 ± 3.15 for attitude, and 33.13 ± 5.19 for practice. In multivariable analyses, primary school education or below (β = −2.626, 95% CI: −4.593 to −0.659, p = 0.009), diagnosis of oesophageal, gastric cardia, or stomach cancer (β = −1.865, 95% CI: −3.278 to −0.452, p = 0.010), colorectal cancer (β = −1.670, 95% CI: −3.299 to −0.041, p = 0.045), and the use of nutritional supplements (β = 1.850, 95% CI: 0.813 to 2.888, p < 0.001) were associated with knowledge scores. Knowledge scores (β = 0.110, 95% CI: 0.066 to 0.154, p < 0.001), being a homemaker (β = −1.660, 95% CI: −2.834 to −0.486, p = 0.006), and the use of nutritional supplements (β = 0.558, 95% CI: 0.019 to 1.096, p = 0.042) were positively associated with attitude scores. For practice, only higher knowledge scores were independently associated with better nutritional practices (β = 0.359, 95% CI: 0.291 to 0.428, p < 0.001). Structural equation modeling showed that knowledge directly influenced attitudes (β = 0.194; p = 0.002) and practices (β = 0.546; p = 0.009).ConclusionPatients diagnosed with malignant tumors exhibited inadequate knowledge and negative attitudes, although the practice was proactive, there was still room for improvement on specific practice. Targeted, multidisciplinary, and continuous nutritional education may be considered to support better nutritional awareness, patient-centered care, and overall quality of life.